Proposal and Preliminary Evaluation of a Usability and UX Multi-Touch Evaluation Technology - Konopatzki, Guilherme Eduardo; Guerino, Guilherme; Valentim, Natasha (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: For multi-touch Information Systems (ISs) to reach the desired level of quality, it is necessary to have an evaluation of it. Two important quality aspects are usability and User eXperience (UX). A good assessment must take into account the specifics of the evaluated context. Problem: Through a Systematic Mapping Study (SMS), it was realized that no usability and UX evaluation technologies take into account the unique characteristics of the multi-touch context. Solution: To solve this gap, the User eXperience and Usability Multi-touch Evaluation Technology (UXUMEQ) was proposed. IS Theory: To fulfill this gap, UXUMEQ was based on Design Theory, which concerns the development and refinement of an artifact. Method: The usability and UX aspects and the evaluation technologies found in the SMS results were selected and evaluated to compose the UXUMEQ. The questions of evaluation technologies found considered relevant were filtered and adapted for the multi-touch context. Results: Therefore, the purpose of UXUMEQ takes into account the specifics of multi-touch, in the form of a modular questionnaire, covering the aspects of usability and UX. Moreover, a preliminary evaluation with three experts in Human-Computer Interaction provided improvements for the UXUMEQ. Contribution: In this way, the existence of usability and UX evaluation technology of ISs that uses multi-touch interaction can contribute to reaching a better quality of this kind of system.